Transferring Data from One EPR to Another: Content – Syntax – Semantic - Bürkle, T.; Schweiger, R.; Altmann, U.; Holena, M.; Blobel, B.; Dudeck, J. (Methods of Information in Medicine, 1999)
When data are transmitted between electronic patient record (EPR) systems, we can distinguish several tasks. One task is the definition of structure and semantic content of the data in a message structure. Another task is the mapping of the sending EPR’s structure to this message structure. A third task is the mapping of the message structure to the receiving EPR’s structure. We describe an approach, which distinguishes clearly between these different tasks and activities. Using this approach we have implemented a data transfer procedure between a cancer registry application and a middleware for healthcare information systems. Our experience showed that the proposed systematic approach helped identify problems for data transfer in an early design phase. It also allowed us to limit modifications of the data exchange procedure to certain tasks or activities when one of the EPR applications was updated. In the end, we could even exchange the underlying message format without having to reimplement the complete interface.
Keywords: Electronic Patient Record; Standards; Communication